Dinâmica de crescimento de uma floresta ombrófila mista em Nova Prata, RS - Moscovich, Fabio Abel (2006)
The changes in the species composition, phytosociological structure and the growth dynamics (recruitment, mortality and dbh increment) have been studied in five permanent plots in a Mixed Araucaria Forest with different degrees of human intervention. The area located in Nova Prata county, Rio Grande do Sul, Brazil, has been measured during the 1995 2003 period, considering trees with diameter at breast height (dbh) over 30 cm. The floristic composition analysis shoes no significant changes during the studied period. Nevertheless, the trends to a lower number of strata indicate changes in the vertical structure, in the sense of a more stable one. The mortality rate has been higher than the recruitment rate and therefore, the dynamics cure not progressive but occurs in periods in which death is greater than inflows, creating gaps in the canopy than can allow the emergence of new individuals. The basal area annual increment can be estimated by an equation developed for the measured forest. Nevertheless, a specific equation had to be developed for Unit 5, that has showed a very different growth pattern, due to the consequences on it of a storm. The result of applying canonic correspondence analysis to the forest is the division in two phytosociological structures, according to the presence, or no, of Araucaria angustifolia. However, no significative changes in the internal phytosociological changes have been observed in these two structures. As observed before, mortality rates have been higher than recruitment rates, noting that this has been higher in the areas with out Araucaria, indicating a higher alteration in theses structures. The annual basal area increments can be estimated through regression equations developed for the two structures. The forest be managed according to the mosaic distribution pattern of the two structures (with and without Araucaria) observed.